Table of Content - - (Journal of Educational and Psychological Sciences, 2025)
Table of Content: 1. Measuring the level of job performance of kindergarten teachers in terms of competence (professional, educational, personal, social) in the city of Makkah Asst-Prof. Shaymah Dakhel Alluhaybi 2. Requirements for transforming Taif University into a green university in light of the experiences of the universities of Wageningen in the Netherlands, Harvard and California Berkeley in the Americas Co-Prof. Hatim Abdullah Al-Hosiny 3. The relationship of entrepreneurial leadership with the development of competitive advantage in private schools in Jeddah from the perspective of teachers and educational supervisors Ms. Shaima Fayez Al-Badri , Co-Prof. Randa Hariri 4. Student Attitudes Towards Jordanian Universities - Reality and Expectations Dr. Asma Maher Qasem 5. The theoretical foundations and educational applications of pragmatist philosophy: An analytical study Dr. Sultan Rajyan Alqathami 6. Psychological Burnout among Kindergarten and First Three Grades Teachers at Rania Governorate in Saudi Arabia Co-Prof. Hadwa Mohmmad Salam Al-Sharari 7. Irrational thoughts and their relation to the psychological stress among mothers of children with an autism spectrum disorder in Al Majma’ah governorate Ms. Manar Sayer Alotaibi